Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 44

Answer

x=-53

Work Step by Step

Simplifying 31 + -2(x + -5) = -3(x + 4) Reorder the terms: 31 + -2(-5 + x) = -3(x + 4) 31 + (-5 * -2 + x * -2) = -3(x + 4) 31 + (10 + -2x) = -3(x + 4) Combine like terms: 31 + 10 = 41 41 + -2x = -3(x + 4) Reorder the terms: 41 + -2x = -3(4 + x) 41 + -2x = (4 * -3 + x * -3) 41 + -2x = (-12 + -3x) Solving 41 + -2x = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 41 + -2x + 3x = -12 + -3x + 3x Combine like terms: -2x + 3x = 1x 41 + 1x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 41 + 1x = -12 + 0 41 + 1x = -12 Add '-41' to each side of the equation. 41 + -41 + 1x = -12 + -41 Combine like terms: 41 + -41 = 0 0 + 1x = -12 + -41 1x = -12 + -41 Combine like terms: -12 + -41 = -53 1x = -53 Divide each side by '1'. x = -53 Simplifying x = -53
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.